Talent management in government in times of economic instability: selected cases from the BRICS countries. Issue 1 (2nd January 2017) - Suk Kim, Pan; Kotchegura, Alexander
Abstract : This paper explores the policies that three BRICS countries used to tackle the growing problem of attracting and retaining talent in public sector institutions. The authors trace the changes in these countries' strategies and approaches resulting from growing budgetary constraints; labour market shifts; new demographic trends; increasing demands for higher performance by public servants; and complex challenges faced by governments worldwide. Although talent management in public sector institutions was a government priority for the three countries—Brazil, China, and Russia—the results achieved have been modest. The authors draw lessons for other governments from their analysis.